AWARENESS OF RISKS FACTORS ASSOCIATED WITH HYPERTENSION IN PATIENTS PRESENTED TO MEDICAL DEPARTMENT OF DHQ HOSPITAL AT DERA GHAZI KHAN - Munazza Batool; Tahira Batool Qaisrani; Javeria Saleem (Journal of University Medical & Dental College, 2016)
ABSTRACT: OBJECTIVE: The present study was conducted to assess the knowledge of modiﬁable risk factors of hypertension among the people of D. G. Khan and to relate the ﬁndings with prevalence of it. METHOD: For the purpose semi- structured questionnaire was designed as a research tool and people were asked for their awareness level in different aspects related to hypertension. Overall 300 respondents among them 185 male and 115 female were taken with age range between 36-50 years. RESULTS: Knowledge regarding association of food (P< 0.020) and smoking (P< 0.052) with hypertension was better in older people. Educated community was well aware about effect of smoking (P< 0.000) and high intake of salt (P< 0.000) as major cause of hypertension. People with good economic values/level had better awareness regarding causes and preventive measures like exercise (P< 0.000) and visiting doctors (P< 0.000). CONCLUSION: It is concluded that with rise in age, education level and economic status awareness regarding preventive and control of hypertension is better.